LIVER FUNCTION AND ANDROGENIC STATUS IN MEN WITH IDIOPATHIC PATHOSPERMIAS - Bondarenko, Volodymyr; Minukhin, Andriy; Skorniyakov, Evgeniy (Problems of Endocrine Pathology, 2012)
Transaminase levels, the total and direct bilirubin, as well as androgenic status indicators in men with idiopathic pathospermias, patients with hypogonadism and practically healthy subjects were analysed. It was established, that alaninaminotransferasa and aspartataminotransferasa enhanced levels were accompanied by decrease in total testosterone and increase in estradiol levels in men with idiopathic sperm concentration defect. Aborementioned patients showed also more essential reduction of free androgen index also more essential reduction of sizes of free androgen index is marked. We revealed slight increase in transaminase levels in men with hypogonadism.